CFD study on Taconis thermoacoustic oscillation with cryogenic hydrogen as working gas. (April 2016) - Sun, Daming; Wang, Kai; Guo, Yinan; Zhang, Jie; Xu, Ya; Zou, Jiang; Zhang, Xiaobin
Highlights: Cross-section averaged parameters in Rott's equations are replaced by local ones. Spatial distributions of key parameters are obtained by using CFD method. Standing-wave component is found to be the source term of Taconis oscillation. Traveling-wave component is found to be the main sink term of Taconis oscillation. Abstract: Taconis oscillation is a kind of typical self-excited thermoacoustic oscillation, the study of which is of great significance to reveal the thermoacoustic conversion effect and find ways to suppress self-excited oscillation in cryogenic systems. Based on computational fluid dynamics (CFD) method, the onset process of Taconis oscillation with low temperature hydrogen at atmospheric pressure as working gas is first simulated. It is shown that a standing-wave acoustic field operating at 91 Hz starts spontaneously and finally develops to a saturation state in the Taconis tube with length and inner diameter of 1 m and 0.01 m respectively. Parametric variations in both axial and radial directions of thermoacoustic field are then studied in detail. By combining the computational results with Rott's theory, the spatial distributions of viscous dissipation, thermal relaxation dissipation, and source/sink terms of Taconis thermoacoustic oscillation are obtained quantitatively. The dissipation and source terms are found to be mainly brought forth by the traveling-wave and standing-wave components of the acoustic field, respectively.